The Development of 21st Century Cultural Intelligence through Discovery Learning and First-Person Historical Presentation - Vinco, Michael Silvester Mitchel; Supriatna, Nana; Mulyana, Agus (History Department, Semarang State University and Historian Society of Indonesia, 2019)
The research was conducted during history learning activity in Year 11 Social 3 (Ilmu Pengetahuan Sosial 3) Santo Fransiskus Asisi Senior High School (a school with Catholic characteristic) on April-June 2018. In some opportunities, this research also included Mujahidin Senior High School (a school with Islamic characteristic). This research used action research methodology with Kemmis & Taggart model. The analysis of data used constructivism learning theories and symbolic interaction theories. This research discusses about various cultural stereotypes which are thriving in West Kalimantan, especially Pontianak. Obstacles in social interaction because of stereotypes among various cultural groups are one of challenges in 21st century that is related to cultural intelligence. First-person historical presentation as one of history education methods is developed in this research. Students involved in this research would be enriched in not only their knowledge, but also their empathy toward various cultural groups. So, this learning is successful in growing studentsÃ¢â‚¬â„¢ cultural intelligence, as can be seen their empathic attitudes and accepting the difference among those various groups.Ã‚Â Penelitian ini dilakukan pada pembelajaran sejarah di kelas 11 Ilmu Pengetahuan Sosial (IPS) 3 SMA Santo Fransiskus Asisi Pontianak (sekolah berciri khas Katolik), pada bulan April-Juni 2018. Pada beberapa kesempatan penelitian ini juga melibatkan SMA Mujahidin Pontianak (sekolah berciri khas Islam). Penelitian ini menggunakan metode penelitian tindakan dengan model Kemmis & Taggart. Analisis data menggunakan teori-teori pembelajaran konstruktivis dan teori interaksi simbolis. Penelitian ini membahas berbagai stereotipe kebudayaan yang berkembang di Kalimantan Barat, khususnya di Kota Pontianak. Hambatan-hambatan di dalam pergaulan sosial karena stereotipe antara berbagai kelompok kebudayaan merupakan salah satu tantangan di abad ke-21 yaitu berkaitan dengan kecerdasan budaya. First-person historical presentation sebagai salah satu metode pendidikan sejarah dikembangkan di dalam penelitian ini. Peserta didik yang terlibat di dalam pendekatan ini akan diperkaya tidak hanya pengetahuan mereka, tetapi juga empati mereka terhadap berbagai kelompok kebudayaan. Dengan demikian pembelajaran ini berhasil menumbuhkan kecerdasan budaya peserta didik. Seperti tampak pada sikap-sikap berempati dan menerima perbedaan di antara beragam kelompok tersebut.Ã‚Â